Pengaruh Model Pembelajaran Kooperatif Berbantuan Media Miniatur Rumah Terhadap Pemahaman Konsep Peserta Didik Pada Materi Rangkaian Listrik di SDN 2 SAPE - Suryani, Irma; Harjono, Ahmad; Khair, Baiq Niswatul (Pendagogia: Jurnal Pendidikan Dasar, 2023)
Science learning is still carried out conventionally and runs in one derection without involving students directly, as well as the lack of use of learning models and media. This study aims to determine the effect of the cooperative learning model assisted by the miniature house media on the understanding of students’ concepts in the electrical circuit material at SDN 2 Sape. The research uses a quantitative approach. The population in this study were 48 students. Data collection technique were carried out by means of a written test. The results of the study obtained an increase in the average number of students from 32.17 to 73.08. based on the results of hypothesis testing, it is obtained that the tcount value is 4.525 while the ttable value is 1.679. Because 4.525 ≥ 1.679, then H0 is rejected and Ha is accepted. This means that there is a significant effect using the miniature house media on understanding of the students’ electric circuit concept.